PENEGAKAN HUKUM TINDAK PIDANA LINGKUNGAN PEMBAKARAN HUTAN DAN LAHAN TERHADAP KORPORASI OLEHKEPOLISIAN DAERAH RIAU RIAU - Ryan Richardo; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Forest fires in Indonesia can not be separated from the poor pattern of land and forest policy in the country. Regular forest fires for a decade are not solely due to changes in ecological links. However, it is influenced by the deliberate element of large-scale plantation business actors in land clearing. Including also the negligence of industrial business actors, and the process of uncontrolled permission to control the territory. This shows that the monitoring and prevention of forest and land fires in Riau province is still very weak. More than 300 fire points in Riau this year are within HTI concession areas and plantations. It shows, the process of issuing permits for the plantation of the government is based on studies that memadai.Sebagai form of responsibility, the government should immediately revoke the operating license in points concessions experiencing the fire. The case of forest and land fires in Riau Province involving corporations that can provide great impact on social life, it should be obliged also to respect the fundamental values of our society which is determined by the criminal law.Based on the description above, the authors take the title of thesis that is